A 4 × 4 Beamforming Network for Spatial Diversity and Multiplexing Reconfiguration - Li Sun; Yuan Gao; Shi-gang Zhou; Guan-xi Zhang; Gao-ang Li (International Journal of Antennas and Propagation)
A simple 4 × 4 beamforming network with spatial diversity and multiplexing reconfiguration is proposed in this paper. By analyzing and decomposing the simplified transmission matrix of the network, it is found that the 4 × 4 butler matrix can achieve spatial diversity and multiplexing reconfiguration by switching the operating modes of the four-port devices. Therefore, by designing a reconfigurable device with three modes among hybrid coupler, crossover, and transmission line, a simple 4 × 4 reconfigurable beamforming network is achieved. The proposed network can achieve orthogonal spatial diversity responses with equal amplitude and progressive phase distribution responses at the four output ports (State 1) and hybrid spatial diversity and multiplexing responses (State 2) with equal amplitude and progressive phase distribution responses at the two adjacent output ports. For the experimental validation, a particular version of the reconfigurable device and network which work at 4.9 GHz, have been designed, fabricated, and tested. Good results indicate the proposed network can be widely used in wireless communication networks for MIMO applications.